2012
DOI: 10.5543/tkda.2012.01753
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic course of a metastatic mass completely filling the right atrium in a patient with hepatocellular carcinoma

Abstract: Intracardiac involvement rarely develops in patients with hepatocellular carcinoma (HCC) and its prognosis is poor. Patients generally have symptoms of sudden dyspnea or massive lower extremity edema and the clinical course may be further complicated by many fatal cardiovascular complications. Absence of cardiac symptoms or findings, however, is an unusual condition. We present a 61-year-old man with HCC who was incidentally found to have an intracavitary mass completely occupying the right atrium. He had no c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Palliative resection may be necessary owing to hemodynamic compromise, but the prognosis remains very poor. In multiple case reports of tumor thrombus resection, there was no improvement in survival or outcomes (3,4). At this time, it is uncertain that resection of tumor thrombus will yield any additional benefit to our patient.…”
Section: Tumor Thrombusmentioning
confidence: 78%
“…Palliative resection may be necessary owing to hemodynamic compromise, but the prognosis remains very poor. In multiple case reports of tumor thrombus resection, there was no improvement in survival or outcomes (3,4). At this time, it is uncertain that resection of tumor thrombus will yield any additional benefit to our patient.…”
Section: Tumor Thrombusmentioning
confidence: 78%
“…Local invasion is more common in cirrhotic patients (5). In the rare cases of HCC with tumor extension to the right atrium and inferior vena cava, most patients were either symptomatic, had cirrhosis, or both (4)(5)(6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…Th ere may be a modest benefi t with radiation, transarterial chemoembolization, or systemic chemotherapy with sorafenib, depending on the size of the lesions (6). Palliative cardiac surgery can be used in cases of cardiac obstruction (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Masci et al [17] Right intraventricular metastasis from HCC in a patient who had undergone a partial hepatectomy for HCC more than two years earlier Systemic chemotherapy with cisplatin and doxorubicin Ulus et al [18] HCC who was incidentally found to have an intracavitary mass completely occupying the right atrium…”
Section: Surgical Ressectionmentioning
confidence: 99%